2001
DOI: 10.1002/ijc.10111
|View full text |Cite
|
Sign up to set email alerts
|

Dietary factors and gastric cancer in Korea: A case‐control study

Abstract: To assess gastric cancer (GC) risk in relation to dietary intake in Korea, a case-control study was performed. Trained dietitians interviewed 136 patients diagnosed with GC, and the same number of controls were selected by matching sex, age and hospital. A significant decrease in GC risk was observed with increased intake of Baiechu kimchi (prepared with salted Chinese cabbage and red pepper, etc.), Baiechu kimchi-stew, garlic, mushroom and soybean milk. On the contrary, a significant increase in the risk of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
160
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(168 citation statements)
references
References 27 publications
6
160
1
1
Order By: Relevance
“…29 Compared with the consistent evidence on anticarcinogenic properties of mushrooms from experimental studies, limited epidemiologic evidence is available and results have been inconclusive. [11][12][13][14][15] Our study provides epidemiologic evidence that dietary mushrooms and its association with green tea decrease breast cancer risk, a finding that is consistent with the laboratory evidence. 9,10 Our results are also consistent with those of 2 case-control studies in Korean women.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…29 Compared with the consistent evidence on anticarcinogenic properties of mushrooms from experimental studies, limited epidemiologic evidence is available and results have been inconclusive. [11][12][13][14][15] Our study provides epidemiologic evidence that dietary mushrooms and its association with green tea decrease breast cancer risk, a finding that is consistent with the laboratory evidence. 9,10 Our results are also consistent with those of 2 case-control studies in Korean women.…”
Section: Discussionsupporting
confidence: 85%
“…Only a few epidemiological studies have examined the association between mushroom intake and cancer. [11][12][13][14][15] Two case-control studies reported a decreased risk of breast cancer associated with dietary mushrooms consumption in Korean women. 14,15 Tea polyphenols, particularly green tea polyphenols, have been demonstrated to possess anticarcinogenic effects against breast cancer in experimental.…”
mentioning
confidence: 99%
“…Probable high risk foods (salted fish, kipper, salted meat, kaleh pache (head and hoof soup)) was confirmed as a risk factor for gastric cancer incidence which is consistent with some studies (Rao et al, 2002;Kim et al, 2002;De Stefani et al, 2004;Strumylaitė et al, 2006). Although frequency, portion size and type of these foods were very important for interpreting of risk factors role, but many studies showed the potential side effects of permanent usage of this kind of foods.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies reported that charred flesh contains mutagen substances which increase risk of gastric cancer (Sugimura et al, 2000;Kim et al, 2002;Farouk Aly, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Six of sixteen studies specifi cally examined the use of table salt, with three reporting statistically signifi cant increased risks (OR = 1.6-6.2 for highest intakes) and two nonsignifi cant ORs. Several recent case-control studies have also revealed an association between salted food and the risk of gastric cancer [20][21][22][23].…”
Section: Evidence From Case-control Studiesmentioning
confidence: 99%